2022
DOI: 10.1109/access.2022.3149295
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning With Variational AutoEncoder for Imbalanced Datasets in Intrusion Detection

Abstract: As a result of the explosion of security attacks and the complexity of modern networks, machine learning (ML) has recently become the favored approach for intrusion detection systems (IDS). However, the ML approach usually faces three challenges: massive attack variants, imbalanced data issues, and appropriate data segmentation. Improper handling of the issues will significantly degrade ML performance, e.g., resulting in high false-negative and low recall rates. Despite many efforts have done in the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Unsupervised learning has shown effectiveness in detecting ransomware in IoMT by identifying novel patterns and anomalies, as demonstrated by Zahoora et al [12] and Lin et al [13]. These studies utilized deep learning techniques like autoencoders and variational autoencoders (VAE) to analyze IoMT data, achieving high detection rates with low false positives.…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…Unsupervised learning has shown effectiveness in detecting ransomware in IoMT by identifying novel patterns and anomalies, as demonstrated by Zahoora et al [12] and Lin et al [13]. These studies utilized deep learning techniques like autoencoders and variational autoencoders (VAE) to analyze IoMT data, achieving high detection rates with low false positives.…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…Imbalanced datasets and improper data segmentation are the main contributors to a loss of the IDS detection accuracy. The authors of [34] proposed a machine learning framework in which they combined a variational autoencoder (VAE) and multilayer perceptron to simultaneously tackle the issues of imbalanced datasets (HDFS and TTP datasets) from multiple data sources and intrusions in complex, heterogeneous network environments. Using a hybrid learning approach, the authors used the variational autoencoder to address the imbalanced datasets issue in the training stage.…”
Section: Related Workmentioning
confidence: 99%
“…While the authors of [34] used a non-traditional approach to solve the data imbalance problem, the authors of [36] used traditional resampling methods (random undersampling, random oversampling, SMOTE, and ADA-SYN) to investigate the influences of these methods on the performance of artificial neural network (ANN) multi-class classifiers using benchmark cybersecurity datasets, including KDD99 and UNSW-NB18. Comparing the performance of the ANN multi-class classifiers using the resampling techniques, their study revealed that undersampling performed better than oversampling in terms of the training time, and oversampling performed better in terms of detecting minority data (abnormal examples).…”
Section: Related Workmentioning
confidence: 99%
“…However, along with numerous benefits, some prejudices have also adhered to these datasets. Lack of appropriate features for IoT, use of malevolent scripts for attack detection, and susceptibility to external cyber malfunctions are some of such enmities [54]. We have adopted the CICIDS2018 dataset which is remarkably known for its spacious range of features towards IoT communications [55,56].…”
Section: Dataset Descriptionmentioning
confidence: 99%